THE RELEVANCE OF SOCIAL SCIENCES: AROUND THE FIGHT AGAINST CRIME - Araujo Frías, Jaime (2014)
Politicians and the general public still believe that punishment is an effective tool in the fight against crime. But current research suggests that this measure not only has been and is still useless in the fight against crime, but also is the most powerful stimulus. On the other hand the most effective responses that have occurred and are suggested to the fight against crime is the assurance and satisfaction of social.